Galectin-3 as an early marker of diastolic dysfunction in children with end-stage renal disease on regular hemodialysis - Akram Elsadek; Mohamed Ibrahim; Asmaa Adel El Fallah; Mohamed Elian; Salem Elsayed Deraz (Wolters Kluwer Medknow Publications, 2022)
Introduction and Aim : Diastolic dysfunction is a common finding in end-stage renal disease (ESRD) on regular hemodialysis (HD). Galectin-3 (Gal-3) has emerged as an early biomarker with diagnostic and prognostic values in cardiac dysfunction with reduced or preserved ejection fraction. We aimed to assess the correlation between Gal-3 levels and diastolic dysfunction in children with ESRD on regular HD. Materials and Methods : Gal-3 levels were assessed in 67 patients on regular HD and 67 healthy controls. Conventional echo-Doppler imaging and tissue-Doppler imaging were done to all patients and control groups. Patients were split into two categories: with or without diastolic dysfunction, based on the early diastolic transmitral velocity to early diastolic mitral annular velocity (E/E') whether more or less than 15, respectively Results : Plasma Gal-3 levels in ng/ml were 16.7 (12.0-22.0) in healthy controls, 15.7 (10.5-22.0) in patients on HD without diastolic dysfunction, and 23.4 (13.4-25.0) in patients on HD with diastolic dysfunction. Gal-3 levels were significantly higher in HD patients with left ventricular diastolic dysfunction (LVDD). Both uni- and multivariate logistic regression analyses revealed that low left ventricular Tei index, low early diastolic mitral annular velocity of lateral wall wave, low early diastolic mitral annular velocity of septal wall wave, high septal early diastolic transmitral velocity to early diastolic mitral annular velocity of lateral wall (E/E') ratio, and high Gal-3 are significant predictors for LVDD in the whole study group. Furthermore, there was a significant positive correlation between the Gal-3 and the grade of diastolic dysfunction. The cut of point of diagnostic accuracy of serum Gal-3 in diastolic dysfunction in HD children was 20.12 with a sensitivity of 93.3 and a specificity 78.4. Conclusions : Gal-3 is a potential early biomarker that can be used in early diagnosis and grading of diastolic dysfunction in ESRD children on regular HD.